Long-Term in vivo Evaluation of Orthotypical and Heterotypical Bioengineered Human Corneas - Garzón, Ingrid; Chato-Astrain, Jesus; González-Gallardo, Carmen; Ionescu, Ana; Cardona, Juan de la Cruz; Mateu, Miguel; Carda, Carmen; Pérez, María del Mar; Martín-Piedra, Miguel Ángel; Alaminos, Miguel (Frontiers in Bioengineering and Biotechnology, 2020)
Purpose: Human cornea substitutes generated by tissue engineering currently require limbal stem cells for the generation of orthotypical epithelial cell cultures. We recently reported that bioengineered corneas can be fabricated in vitro from a heterotypical source obtained from Wharton’s jelly in the human umbilical cord (HWJSC). Methods: Here, we generated a partial thickness cornea model based on plastic compression nanostructured fibrin-agarose biomaterials with cornea epithelial cells on top, as an orthotypical model (HOC), or with HWJSC, as a heterotypical model (HHC), and determined their potential in vivo usefulness by implantation in an animal model. Results: No major side effects were seen 3 and 12 months after implantation of either bioengineered partial cornea model in rabbit corneas. Clinical results determined by slit lamp and optical coherence tomography were positive after 12 months. Histological and immunohistochemical findings demonstrated that in vitro HOC and HHC had moderate levels of stromal and epithelial cell marker expression, whereas in vivo grafted corneas were more similar to control corneas. Conclusions: These results suggest that both models are potentially useful to treat diseases requiring anterior cornea replacement, and that HHC may be an efficient alternative to the use of HOC which circumvents the need to generate cornea epithelial cell cultures.